El nuevo realismo la filosofía del siglo XXI - Ramírez, Mario Teodoro (Filosofía, 2016)
So far this century has been shaping a new philosophical movement that proposes a radical change, a turn of 180 degrees with respect to what was now accepted as being in the philosophical field and in the theoretical field in general. This is what has been called the "new realism," although it has also accepted other meanings, such as new materialism, speculative materialism, speculative realism, ontological realism or neutral realism, according to the different versions that have been presented. Certainly, as with other philosophical movements, the new realism does not constitute a unified movement: it has only just begun and divergent positions have begun to emerge. However, all these positions have some basic coincidences. The new realism is shaping an emerging paradigm in the philosophical thought that comes to question - and in principle to define, that is, to delineate - the paradigm of the whole modern philosophy and its radicalization in the so-called postmodernity. Although the question of what will be the new realism is open, an already relevant acquisition of its emergence, which has in principle negative character, is that it allows us to place ourselves, perhaps for the first time, against the totality of modern philosophy in Its various variants, to specify their basic and common assumptions, and to specify fundamental critical points